Understanding “Hijrah and Atonement” among Indonesian Celebrities: Social Psychology and Psychology of Religion Perspectives - Gazi Saloom (Jurnal Dialog, 2021)
This article aims at understanding “hijrah and Atonement” from the perspectives of psychology in particular psychology of religion. This article focuses to investigate the phenomena of young people who conduct hijrah and the process of their hijrah? This article is part of the qualitative studies on religious conversion among young generations including those are among Indonesian celebrities. Data and information are gathered from various online news and social media particularly from YouTube as the main source. Two main figures of Indonesian celebrities are chosen to be subjects of the study by using their life stories and statements about religious conversion in various online news and social media, and then those of stories and statements are analyzed with thematic analysis technique. This paper finds that the choice of religious conversion takes place through a long psychological and social process. Starting from a psychological crisis in a personal and interpersonal context and ending with a strong commitment and acceptance facing the consequences of their decision. The pivotal conclusion of this study addresses that hijrah is a long process of seeking God and constructing meaningfulness. Keywords: emigration, psychology, conversion, millennial Tulisan ini bertujuan untuk memahami fenomena hijrah dari sudut pandang ilmu psikologi, terutama mencaritahu mengapa anak muda pesohor Indonesia tertarik untuk berhijrah dan bagaimana proses mereka berhijrah? Tulisan ini adalah hasil studi kualitatif tentang konversi agama di kalangan generasi milineal terutama di kalangan pesohor Indonesia. Data dikumpulkan dari berbagai berita online dan media sosial terutama Youtube sebagai sumber informasi. 2 tokoh pesohor Indonesia papan atas dipilih sebagai subyek studi dengan mengkaji pengalaman hidup dan pernyataannya terkait konversi agama di pemberitaan online dan media sosial lalu dianalisis dengan teknik analisis tematik.. Studi ini menemukan bahwa pilihan melakukan konversi keagamaan berlangsung melalui proses psikologis dan sosial yang panjang. Dimulai dari krisis psikologis dalam konteks personal dan interpersonal dan berakhir dengan komitmen yang kuat dan penerimaan konsekuensi dari keputusan berhijrah. Kesimpulan penting dari penelitian ini adalah bahwa hijrah merupakan perjanalan spiritual yang panjang dalam mencari Tuhan dan Kebermaknaan dengan segala cobaan dan tantangan yang mengikutinya. Kata Kunci: hijrah, psikologi, konversi, milineal